Historyczno-prawne uwarunkowania utworzenia przez Henryka VIII angielskiego Kościoła państwowego w 1534 r. - Grzebyk, Tomasz (Saeculum Christianum. Pismo Historyczne, 2019)
The origins of the reformation in England are inseparably join to king Henry VIII. This character works in common human imagination is a bloody tyrant, who strives to satisfy his desires and ambitions. In a certain sense, his character traits affected his decisions. It is important to write, that the history of England abounds many examples of kings, who wants to got domination on church. In this article author by the analysis of medieval English law and other historical conditions, presents his thesis as an introduction to passing The Act of Supremacy in 1534.